2019
DOI: 10.1107/s1600576719005521
|View full text |Cite|
|
Sign up to set email alerts
|

Detailed surface analysis of V-defects in GaN films on patterned silicon(111) substrates by metal–organic chemical vapour deposition

Abstract: An error in the article by Gao, Zhang, Zhu, Wu, Mo, Pan, Liu & Jiang [J. Appl. Cryst. (2019), 52, 637–642] is corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This indicates that the V-pits of sample 2 has higher potential barrier height that suppresses non-radiative recombination functionally. Previously, a series of reports suggested that the height of this barrier mainly depends on the size of V-pits [30], [31], [32]. However, in this experiment, it has been demonstrated through SEM that there is no significant difference in the V-pits size between sample 1 and sample 2.…”
Section: Resultsmentioning
confidence: 52%
“…This indicates that the V-pits of sample 2 has higher potential barrier height that suppresses non-radiative recombination functionally. Previously, a series of reports suggested that the height of this barrier mainly depends on the size of V-pits [30], [31], [32]. However, in this experiment, it has been demonstrated through SEM that there is no significant difference in the V-pits size between sample 1 and sample 2.…”
Section: Resultsmentioning
confidence: 52%
“…According to the measurement results, the proportion of the V-shaped pit is approximately 30% of surface area corresponding to the fifth (blue) QW in LED S1, and the proportion of the V-shaped pit is approximately 10% of surface area corresponding to the first (green) QW in LED S1. The detailed measurement method was reported previously [23]. Thus, the difference between the ranges of influence of the horizontal electric fields of the blue QW and that of the green QWs is large.…”
Section: Asmentioning
confidence: 99%
“…As a result, most commercial InGaN-based LEDs have V-shaped pits in the structure. Normally, the V-shaped pits are formed in the pre-layer with low growth temperature and high growth rate before multi-quantum wells (MQWs) [22][23][24][25]. Then, the subsequent grown MQWs can have two different shapes: the tilted MQWs on the pit side and the flat MQWs on the terrace.…”
Section: Introductionmentioning
confidence: 99%